Present Foreign Policy of Lithuania - A N Sytin (Vestnik RUDN. International Relations, 2010)
Article is devoted to various aspects of Lithuanian foreign policy after parliamentary 2008 and presidential 2009 elections, in particular relations of Lithuania with Russia and the European Union. The main attention is paid to the interdependence of Lithuanian internal and foreign policy.